Los conocimientos previos y su importancia en la construcción de aprendizajes significativos, en la asignatura de Química. Año lectivo 2022-2023 - López Girón, Jaime Enrique (2023)
Prior knowledge is consider as the previous knowledge that students have at the beginning of each class, such knowledge is related to new knowledge to achieve significant learning and not from memory. This research work is presented to enhance significative learning achievement in students, through constructivist didactic strategies focused in prior knowledge that allow to improve the development of learning experiences of Chemistry in the first year of baccalaureate of “Pio Jaramillo Alvarado” educative unit, academic year 2022-2023. During the research, qualitative approach was used both with inductive method, because it is focused in the understanding and comprehension of the identified problem. For the nature of information, it is Participative Action Research, due to the study reality was intervened, thus, it is a transversal type for the determined period of time in which it was developed. To answer the proposed problem, different techniques and research instruments were applied for the data collection such as survey and diagnostic and procedural interviews. During the development of the research, micro curricular planning (Lesson plans) was made and executed, in which different techniques were applied with the aim of inquire prior knowledge, both with constructivist didactic strategies to enhance significative learning achievement. The analysis of the reached results allowed to determine that, to inquire the prior knowledge, there are techniques that allow to elaborate new concepts that come from them. As a result of the research, the techniques that stood out were: random questions, and case study; regarding the didactic strategies, the most relevant were interactive illustrative and collaborative learning that demonstrate a remarkable effectiveness to build significative learning. Keywords: constructivist didactic strategies, techniques to investigate knowledge, significative learning, life experiences.